Inorganic solid electrolyte, preparation method thereof and lithium secondary battery

By forming a solid solution on the surface of the halide solid electrolyte with the nano-scale oxide solid electrolyte, the problems of stability and ionic conductivity of the halide solid electrolyte in lithium secondary batteries are solved, and the preparation of an inorganic solid electrolyte with high conductivity and stability is achieved.

CN119725697APending Publication Date: 2025-03-28BEIJING FUAN LEZHANG NEW ENERGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411708965.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The halide solid electrolyte has problems with stability and ionic conductivity in lithium secondary batteries, and the ionic conductivity of the oxide solid electrolyte is low and unstable.

Method used

By forming a solid solution in a nano-scale oxide solid electrolyte with a halide solid electrolyte, a part of the solid electrolyte is coated on the surface of the halide solid electrolyte, combined with high energy ball milling method and sintering technology, an inorganic solid electrolyte with high conductivity and stability is prepared.

Benefits of technology

It is achieved to improve the stability of the electrolyte while improving the ionic conductivity, enhance the diffusion rate of lithium ions, and improve the cycle performance and service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725697A_ABST
    Figure CN119725697A_ABST
Patent Text Reader

Abstract

The invention provides an inorganic solid electrolyte, a preparation method thereof and a lithium secondary battery. The inorganic solid-state electrolyte comprises an oxide solid-state electrolyte and a halide solid-state electrolyte, and the oxide solid-state electrolyte and the halide solid-state electrolyte are both lithium-containing solid-state electrolytes; wherein the oxide solid electrolyte at least partially coats the surface of the halide solid electrolyte; the oxide solid electrolyte and the halide solid electrolyte at least partially form a solid solution state to realize the coating; the particle size of the oxide solid electrolyte is 100 to 1000 nm; the molar ratio of the oxide solid electrolyte to the halide solid electrolyte is (1: 99)-(90: 10).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an inorganic solid electrolyte and a preparation method thereof and a lithium secondary battery, belonging to the field of lithium ion batteries. Background Art

[0002] Solid-state lithium batteries have become the inevitable path for the development of lithium batteries in the future due to their advantages such as high safety and high energy density. Solid-state electrolytes are one of the core components of solid-state lithium batteries. Inorganic solid-state electrolytes have become a research hotspot in solid-state electrolytes due to their advantages such as good ionic conductivity, negligible electronic conductivity, and a wide electrochemical window. Among inorganic solid-state electrolytes, oxide electrolytes have been widely studied due to their advantages such as good air stability and smooth ion transport. However, oxide electrolytes have the problem of low room temperature ionic conductivity.

[0003] Halide solid electrolytes are a new type of solid electrolyte that has been developed in recent years. They have good ionic conductivity, a wide electrochemical window, excellent stability to high-voltage oxide cathodes, and halides have certain advantages in processing technology and raw material costs. However, the electrochemical stability of halide solid electrolytes and metal lithium anodes is poor, which can easily cause side reactions in the solid-state battery cycle, leading to problems such as structural damage to the solid electrolyte, reduced cycle stability, and battery failure.

[0004] Reference 1 discloses a halide solid electrolyte material, which is prepared by introducing oxygen element by adding an oxidant into a Li-Me-X type halide solid electrolyte to form a Li a MeX b O c The halide solid electrolyte has improved the air stability of the halide solid electrolyte. However, Li-Me-X type halides have the characteristics of too strong coordination ability between the element Me and oxygen atoms, so when the oxidant is introduced, it is easy to produce Me-OX heterophase compounds, which may lead to a decrease in the ionic conductivity of the halide solid electrolyte material.

[0005] In addition, composite solid electrolytes are also prepared by blending methods. For example, Reference 2 discloses a composite solid electrolyte, which includes: a halide solid electrolyte; and a coating layer, which is arranged on the surface of the halide solid electrolyte, and the coating layer includes an oxide solid electrolyte. A composite solid electrolyte is obtained by coating a high-pressure-resistant oxide solid electrolyte on the surface of a low-pressure-resistant halide solid electrolyte. The composite solid electrolyte under the set relationship has both the high ion conductivity of the halide solid electrolyte and the high pressure resistance of the oxide solid electrolyte, which reduces the possibility of decomposition of the composite solid electrolyte and helps to improve the service life and cycle stability of the battery.

[0006] Reference 3 discloses a composite solid electrolyte, which includes: forming a halide electrolyte film on the surface of oxide electrolyte particles or electrode particles. The halide solid electrolyte reduces the grain boundary impedance and interface impedance of the oxide solid electrolyte, thereby improving its electrochemical performance. However, this method cannot solve the problem of surface instability of the halide solid electrolyte.

[0007] It can be seen that although a series of studies have been conducted on inorganic solid electrolytes, there is still room for further research on the preparation of inorganic solid electrolytes with both high ionic conductivity and high air stability.

[0008] References:

[0009] Reference 1: CN112838264A

[0010] Reference 2: CN117613368A

[0011] Reference 3: CN111509293A Summary of the invention

[0012] Problem that the invention aims to solve

[0013] As mentioned above, halide solid electrolytes have high ionic conductivity, but due to the intrinsic defects caused by transition metals, they are very unstable to lithium metal negative electrodes and have poor stability in the air, especially they are very sensitive to water molecules; although oxide solid electrolytes have high stability to lithium negative electrodes and air, their ionic conductivity is low.

[0014] Further, as in Reference 2, a halide solid electrolyte and an oxide solid electrolyte are directly mixed by spherical film to form a composite solid electrolyte having an oxide solid electrolyte coating layer. However, in fact, due to this core-shell structure, although uniform coating can be achieved by methods such as ball milling, in the practice of the present applicant, it is also found that since the core and the shell are usually mainly physically bonded under their preparation conditions, and since the core and the shell are not the same in terms of thermal expansion coefficient, cohesion, etc., during use, especially after multiple charge and discharge cycles, the stability of the core-shell structure also decays, resulting in a decrease in battery performance.

[0015] In order to solve the above problems, the present invention provides an inorganic solid electrolyte, which achieves the purpose of simultaneously improving material stability and ionic conductivity by forming a solid solution state with a halide solid electrolyte at least partially with a nano-scale oxide solid electrolyte and coating it on the surface of the halide solid electrolyte.

[0016] Furthermore, the present invention also provides a method for preparing an inorganic solid electrolyte, which achieves the formation of a two-phase solid solution of an oxide solid electrolyte and a halide solid electrolyte through an improved high-energy ball milling method, thereby forming an oxyhalide solid electrolyte material with a stable surface and high internal conductivity, thereby achieving a combination of the advantages of an oxide solid electrolyte and a halide solid electrolyte.

[0017] In addition, the present invention also provides a lithium secondary battery, which includes a positive electrode, a negative electrode and the above-mentioned inorganic solid electrolyte.

[0018] Solutions for solving problems

[0019] The present invention first provides an inorganic solid electrolyte, wherein the inorganic solid electrolyte includes an oxide solid electrolyte and a halide solid electrolyte, and the oxide solid electrolyte and the halide solid electrolyte are both lithium-containing solid electrolytes;

[0020] Wherein, the oxide solid electrolyte at least partially covers the surface of the halide solid electrolyte;

[0021] The oxide solid electrolyte and the halide solid electrolyte at least partially form a solid solution state to achieve the coating;

[0022] The particle size of the oxide solid electrolyte is 100 to 1000 nm;

[0023] The molar ratio of the oxide solid electrolyte to the halide solid electrolyte is 1:99 to 90:10.

[0024] According to the inorganic solid electrolyte of the present invention, the halide solid electrolyte has a composition formula of Li x MX y express,

[0025] Wherein, M represents one or more metal elements, and M includes at least one metal element M1 selected from Zr, In, Y, and Sc;

[0026] X represents a halogen element,

[0027] The total number of positive valences of the metal element M is z, y=x+z.

[0028] According to the inorganic solid electrolyte of the present invention, the M further includes a doping element M2, and the doping element M2 includes a combination of one or more of Mg, Fe, Mn, Al, Cr, and Ti.

[0029] According to the inorganic solid electrolyte of the present invention, wherein the X is selected from one of Br, Cl or I.

[0030] According to the inorganic solid electrolyte of the present invention, the oxide solid electrolyte is crystalline or amorphous.

[0031] According to the inorganic solid electrolyte of the present invention, the oxide solid electrolyte is selected from at least one of NASICON type, perovskite type, garnet type and LISICON type.

[0032] In addition, the present invention also provides a method for preparing the inorganic solid electrolyte according to the present invention, which comprises the following steps:

[0033] Mixing the synthetic raw material of the halide solid electrolyte and the oxide solid electrolyte with a solvent to obtain a mixture;

[0034] High-energy ball milling the mixture to form a precursor;

[0035] The precursor is sintered to obtain an inorganic solid electrolyte.

[0036] According to the preparation method of the present invention, during the high-energy ball milling process, the rotation speed is 300 to 800 rpm / min, and the ball milling time is 10 to 45 hours.

[0037] Furthermore, the present invention also provides a lithium secondary battery, wherein the lithium secondary battery comprises a positive electrode, a negative electrode and the inorganic solid electrolyte according to the present invention.

[0038] According to the lithium secondary battery of the present invention, the negative electrode is a lithium negative electrode.

[0039] Effects of the Invention

[0040] By implementing the above technical solution, the present invention can achieve the following technical effects:

[0041] 1) The inorganic solid electrolyte provided by the present invention forms a solid solution of nano-scale oxide solid electrolyte and halide solid electrolyte and is coated on the surface of halide solid electrolyte, thereby introducing halogen elements with weak electronegativity, thereby increasing the diffusion rate of lithium ions and achieving the purpose of improving stability while improving ionic conductivity;

[0042] 2) The interaction between the monovalent halogen anions and lithium ions in the halide solid electrolyte is weaker than that between the divalent sulfur or oxygen anions, so it is expected to achieve rapid lithium ion transport; in addition, the larger radius of the halogen anions leads to longer ionic bonds and greater polarizability in the compound, which is beneficial to the migration of lithium ions and improves the plasticity of the electrolyte;

[0043] 3) The inorganic solid electrolyte provided by the present invention is stable to the lithium negative electrode and can exist stably in dry air. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 A schematic structural diagram of the inorganic solid electrolyte of Example 1 of the present invention is shown. DETAILED DESCRIPTION

[0045] The following is a detailed description of the present invention. The following description of the technical features is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:

[0046] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0047] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.

[0048] In this specification, the word "may" includes both performing a certain process and not performing a certain process.

[0049] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.

[0050] In this specification, the "normal temperature" or "room temperature" used means an indoor ambient temperature of "23±2°C".

[0051] In this specification, the unit names used are all international standard unit names, and unless otherwise stated, the "%" used indicates weight or mass percentage.

[0052] In the present specification, the use of “substantially” or “essentially” means that the standard deviation from a theoretical model, theoretical data or target data is within a numerical range of 1%, preferably 0.8%, and more preferably 0.5%.

[0053] In this specification, when the terms “include” and / or “comprise” are used, they indicate the existence of features, steps, operations, devices, components and / or their combinations.

[0054] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0055] The present invention mainly provides an inorganic solid electrolyte and a preparation method thereof, which combines the advantages of the oxide solid electrolyte and the halide solid electrolyte by coating the oxide solid electrolyte on the surface of the halide solid electrolyte, thereby achieving the purpose of improving stability while improving ionic conductivity.

[0056] The present invention is mainly obtained through the following insights:

[0057] It is known that halide solid electrolytes have high ionic conductivity, but due to the intrinsic defects caused by transition metals, they are very unstable to lithium metal negative electrodes and have poor stability in the air, especially very sensitive to water molecules; although oxide solid electrolytes have high stability to lithium negative electrodes and air, their ionic conductivity is low. In halide solid electrolytes, simply introducing an oxidant to improve air stability may lead to a decrease in the ionic conductivity of halide solid electrolyte materials. In addition, by simply physically coating the oxide solid electrolyte on the surface of the halide solid electrolyte, the improvement of its electrochemical performance may be significantly attenuated as it is used, and the cycle performance cannot be effectively improved. The inventors found through research that by forming a partial solid solution state of a nano-scale oxide solid electrolyte and a halide solid electrolyte coated on the surface of the halide solid electrolyte, a material with high conductivity inside and high stability outside can be formed, thereby simultaneously improving material stability and ionic conductivity.

[0058] Furthermore, the preparation method provided by the present invention can, through high-energy ball milling and sintering, simultaneously synthesize the halide solid electrolyte and coat the nanoscale oxide solid electrolyte on the surface of the halide solid electrolyte during the synthesis process, thereby forming a partial solid solution state of the oxide solid electrolyte and the halide solid electrolyte.

[0059] <First aspect>

[0060] A first aspect of the present invention provides an inorganic solid electrolyte, which includes an oxide solid electrolyte and a halide solid electrolyte; wherein the oxide solid electrolyte is coated on the surface of the halide solid electrolyte.

[0061] It should be noted that other functional additives may also be added without affecting the performance of the inorganic solid electrolyte or the technical effect of the present invention.

[0062] As for the coating method, the oxide solid electrolyte and the halide solid electrolyte are coated by at least partially forming a solid solution state. The solid solution state mainly refers to the halide solid electrolyte of the present invention and at least a part or all of the oxide solid electrolyte on its surface being combined at the atomic level, and preferably, in the area where the solid solution state is formed, a substantially homogeneous state is formed in the circumferential direction. Through the coating of the solid solution state, the compatibility of the interface between the two phases can be improved and the interface impedance can be reduced.

[0063] Halide solid electrolyte

[0064] The halide solid electrolyte of the present invention is provided as a high-conductivity material inside an inorganic solid electrolyte.

[0065] The halide solid electrolyte has a composition formula of Li x MX y express,

[0066] Wherein, M represents a metal element. The metal element M in the present invention includes at least a basic metal element M1 and optionally, may also include other doping metal elements M2.

[0067] For M1, in some specific embodiments, it may include a combination of one or more of Zr, In, Y and Sc. Preferably, the M1 may be Zr or at least partially include Zr.

[0068] In addition, there is no particular limitation on the doping element M2 that can be used in principle. In some specific embodiments of the present invention, the doping element M2 may include a combination of one or more of Mg, Fe, Mn, Al, Cr, and Ti.

[0069] Furthermore, X represents a halogen element, such as F, Cl, Br, I. From the perspective of increasing the diffusion rate of lithium ions, X is preferably a halogen element with a weaker electronegativity, such as one or more of Cl, Br, I, etc., and from the perspective of ease of acquisition and atomic radius, X in the present invention is preferably Cl.

[0070] There is no particular limitation on x and y. The total positive valence number of the metal M is z, and y=x+z. In some preferred embodiments, y=6, and x=2 or 3.

[0071] In some specific embodiments, the halide solid electrolyte is selected from a combination of one or more of Li2ZrCl6, Li3YCl6, Li3InCl6, Li3YbCl6, Li3ScCl6, and Li3YBr6.

[0072] Oxide solid electrolyte

[0073] The oxide solid electrolyte of the present invention is coated as a coating layer (at least partially forming a solid solution state) on the surface of the above-mentioned halide solid electrolyte, which does not affect its conductivity while also improving the stability of the halide solid electrolyte. The obtained inorganic solid electrolyte can have the advantages of both halide solid electrolyte and oxide solid electrolyte, and has excellent ionic conductivity and stability to air and lithium negative electrodes.

[0074] There is actually no particular restriction on the type of the oxide solid electrolyte, which may be a crystalline or amorphous oxide solid electrolyte. Considering stability, it is preferred to use a crystalline oxide solid electrolyte, such as at least one of NASICON type, perovskite type, garnet type and LISICON type, among which perovskite type or garnet type is more preferred.

[0075] In some specific embodiments, the oxide solid electrolyte can be selected from lithium lanthanum zirconium oxide (LLZO) and modified materials, such as niobium-doped lithium lanthanum zirconium oxide (LLZNO), tantalum-doped lithium lanthanum zirconium oxide (LLZTO), niobium-tantalum dual-doped lithium lanthanum zirconium oxide (LLZNTO), etc., as well as one or more of lithium lanthanum titanoxide (LLTO), lithium aluminum titanium phosphate (LATP), lithium yttrium titanium phosphate (LYTP), lithium aluminum germanium phosphate (LAGP), and lithium aluminum oxide (LiAlO2).

[0076] The particle size of the oxide solid electrolyte may be 100 to 1000 nm, preferably 100 to 500 nm, for example, 200 nm, 300 nm, 400 nm, 600 nm, 700 nm, 800 nm, 900 nm, etc.

[0077] Composition and morphology of inorganic solid electrolytes

[0078] Regarding the composition of the inorganic solid electrolyte, the molar ratio of the oxide solid electrolyte to the halide solid electrolyte is 1:99 to 90:10, preferably 10:90 to 50:50, for example, 5:95, 15:85, 20:80, 25:75, 30:70, 35:65, 40:60, 60:40, 70:30, 80:20, etc. By setting such a ratio, a coating structure can be better formed.

[0079] Further, as the inorganic solid electrolyte of the present invention, it mainly includes a halide solid electrolyte as a core part and a solid solution layer covering the core. Optionally, in addition to the solid solution layer, the inorganic solid electrolyte of the present invention also allows the presence of a non-solid solution oxide solid electrolyte layer on the surface, which can be on the surface of the solid solution layer or in direct contact with the above-mentioned core.

[0080] The solid solution layer of the present invention can be formed by solid solution of at least part or all of the oxide solid electrolyte and the halide solid electrolyte. In some preferred embodiments of the present invention, more than 80 mass %, preferably more than 90 mass %, and more preferably more than 95 mass % of the oxide solid electrolyte is present in the solid solution layer.

[0081] In the solid solution layer of the present invention, the material composition is substantially uniform in the circumferential direction. In addition, a concentration gradient of the metal element in the oxide solid electrolyte is allowed to exist in the radial direction.

[0082] Furthermore, for the solid solution layer of the present invention, there is no particular limitation on its thickness in principle. In some specific embodiments of the present invention, it can be less than 300 nm, preferably less than 250 nm, and more preferably less than 200 nm, for example, 2-180 nm, 5-150 nm, 10-120 nm, 15-100 nm, etc.

[0083] In addition, the solid solution layer of the present invention can protect the halide solid electrolyte core at a level of 50 area % or more, preferably 60 area % or more, and more preferably 70 area % or more.

[0084] <Second Aspect>

[0085] The second aspect of the present invention provides a method for preparing the inorganic solid electrolyte described in the first aspect.

[0086] It should be noted that, as long as the inorganic solid electrolyte can be formed into the form defined in the <First Aspect> of the present invention, there is no particular limitation on the preparation method thereof in principle.

[0087] However, from the perspective of preparation convenience and high efficiency, the present invention exemplarily provides a method for preparing a suitable inorganic electrolyte, specifically, it comprises the following steps:

[0088] Mixing the synthetic raw material of the halide solid electrolyte and the oxide solid electrolyte with a solvent to obtain a mixture;

[0089] High-energy ball milling the mixture to form a precursor;

[0090] The precursor is sintered to obtain an inorganic solid electrolyte.

[0091] Different from the aforementioned reference 1 in which the halide solid electrolyte and the oxide solid electrolyte are directly blended by ball milling, the present invention actually blends the precursor of the halide solid electrolyte with the oxide solid electrolyte.

[0092] That is, the present invention adopts the method of high-energy ball milling and sintering to simultaneously (in situ) coat the oxide solid electrolyte on the surface of the halide solid electrolyte during the synthesis of the halide solid electrolyte to form a partial solid solution state, thereby improving the interface characteristics and realizing the synthesis and preparation of the inorganic solid electrolyte with high conductivity and excellent stability.

[0093] The types of the halide solid electrolyte and the oxide solid electrolyte are the same as those in the first aspect and will not be described in detail here.

[0094] There is no particular limitation on the raw materials for synthesizing the halide solid electrolyte, and they can be selected as needed. For example, lithium halide and metal halide can be used. The ratio of the raw materials for synthesizing the halide solid electrolyte can be selected according to the desired halide solid electrolyte.

[0095] The type of the solvent is not particularly limited and can be selected as needed, for example, it can be one or more of ethanol, isopropanol, N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), etc. As for the amount of the solvent, from the perspective of sufficient dissolution, the solid-liquid ratio can be 1: (0.5-10), preferably 1: 1-1: 3.

[0096] For the high-energy ball milling step, the rotation speed can be 300-800 rpm / min, for example, 400 rpm / min, 500 rpm / min, 600 rpm / min, 700 rpm / min, etc.; the ball milling time can be 10-45 h, for example, 15 h, 20 h, 25 h, 30 h, 35 h, 40 h, etc.

[0097] There is no particular limitation on the grinding balls, which can be selected as needed. For example, the grinding balls can be zirconium oxide or other commonly used grinding balls in the art, and the ball-to-material ratio can be 1:1 to 15:1.

[0098] In order to improve product uniformity and grinding effect, a forward and reverse cycle can be set. In some specific implementation schemes, the forward and reverse time can be 10 to 50 minutes as a switching cycle, and the forward and reverse cycle can be repeated 20 to 40 times; in addition, an intermittent time can also be set, and the intermittent time can be 5 to 20 minutes.

[0099] In the sintering step, the sintering temperature is 150-300°C, such as 180°C, 200°C, 220°C, 250°C, 280°C, etc.; the sintering time is 2-8h, such as 3h, 4h, 5h, 6h, 7h, etc.

[0100] In some specific embodiments, the high-energy ball milling and sintering steps can be performed under the protection of an inert gas to improve the purity of the product. The inert gas is not particularly limited and can be an inert gas commonly used in the art.

[0101] <Third Aspect>

[0102] The third aspect of the present invention provides a lithium secondary battery, in particular a lithium secondary battery comprising or using the inorganic solid electrolyte described in the first aspect of the present invention or the inorganic solid electrolyte prepared according to the preparation method described in the second aspect.

[0103] Such a lithium secondary battery includes at least a positive electrode, a negative electrode, and a solid electrolyte.

[0104] The positive electrode may include various positive electrode active materials, such as ternary lithium oxide active materials and lithium iron phosphate active materials.

[0105] For the negative electrode, various negative electrode materials such as graphite, silicon, and metal lithium can be used. In some specific embodiments, the negative electrode is a lithium negative electrode.

[0106] For the solid electrolyte, other solid electrolyte materials other than the inorganic solid electrolyte of the present invention may be used without affecting the technical effect of the present invention.

[0107] The above-mentioned lithium secondary battery of the present invention can be used as a battery for personal consumer electronic products, such as laptops, tablet computers, mobile phones, drones, lighting equipment, mobile power storage and the like, and can also be used as a power battery, such as a battery for electric vehicles, hybrid vehicles, passenger / cargo aircraft and the like.

[0108] Example

[0109] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0110] Example 1

[0111] LLZTOCl(aLi 6.5 LqCy 1.5 Ta 0.5 O 12 ·bLi2ZrCl6=

[0112] Li 6.5a+2b La 3aZr 1.5a+b Ta 0.5a O 12a Cl 6b , a: b = 1: 4) preparation method:

[0113] Weigh a total of 10g of nano-oxide electrolyte materials LLZTO, LiCl and ZrCl4, where the molar ratio of LLZTO to Li2ZrCl6 is 1:4 (the molar ratio of LiCl to ZrCl4 is 2:1), add 20g of isopropanol into a ball mill, and a certain amount of zirconium oxide grinding balls (ball-to-material ratio 5:1). Under the protection of inert gas, rotate forward at a speed of 500rpm / min for 30min and then stop for 10min, then reverse for 30min and then stop for 10min, repeat 30 times in total, and after mixing, vacuum dry into powder, then put it into a tube furnace and sinter it at 200℃ for 5h in an Ar atmosphere. After sintering, the inorganic solid electrolyte solid solution material LLZTOCl can be obtained.

[0114] Example 2

[0115] LLZTOCl(aLi 6.5 Ln3Z 1.5 Ta 0.5 O 12 ·bLi2ZrCl6=

[0116] Li 6.5a+2b La 3a Zr 1.5a+b Ta 0.5a O 12a Cl 6b , a: b = 3: 7) preparation method:

[0117] Weigh a total of 10g of nano-oxide electrolyte materials LLZTO, LiCl and ZrCl4, where the molar ratio of LLZTO to Li2ZrCl6 is 3:7 (the molar ratio of LiCl to ZrCl4 is 2:1), add 20g of isopropanol into a ball mill, and a certain amount of zirconium oxide grinding balls (ball-to-material ratio 5:1). Under the protection of inert gas, rotate forward at a speed of 500rpm / min for 30min and then stop for 10min, then reverse for 30min and then stop for 10min, repeat 30 times in total, and after mixing, vacuum dry into powder, then put it into a tubular furnace and sinter it at 200℃ for 5h in an Ar atmosphere. After sintering, the inorganic solid electrolyte solid solution material LLZTOCl can be obtained.

[0118] Example 3

[0119] LLZTOCl(aLi 6.5 Ln3Z 1.5 Ta 0.5 O12 ·bLi2ZrCl6=

[0120] Li 6.5a+2b La 3a Zr 1.5a+b Ta 0.5a O 12a Cl 6b , a: b = 1: 1) preparation method:

[0121] Weigh a total of 10g of nano-oxide electrolyte materials LLZTO, LiCl and ZrCl4, where the molar ratio of LLZTO to Li2ZrCl6 is 1:1 (the molar ratio of LiCl to ZrCl4 is 2:1), add 20g of isopropanol into a ball mill, and a certain amount of zirconium oxide grinding balls (ball-to-material ratio 5:1). Under the protection of inert gas, rotate forward at a speed of 500rpm / min for 30min and then stop for 10min, then reverse for 30min and then stop for 10min, repeat 30 times in total, and after mixing, vacuum dry into powder, then put it into a tubular furnace and sinter it at 200℃ for 5h in an Ar atmosphere. After sintering, the inorganic solid electrolyte solid solution material LLZTOCl can be obtained.

[0122] Example 4

[0123] LLZTYOCl(aLi 6.5 Ln3Z 1.5 Ta 0.5 O 12 ·bLi2YCl6=

[0124] Li 6.5a+2b La 3a Zr 1.5a Ta 0.5a Y b O 12a Cl 6b , a: b = 1: 4) preparation method:

[0125] Weigh a total of 10g of nano-oxide electrolyte materials LLZTO, LiCl and YCl3, where the molar ratio of LLZTO to Li2YCl6 is 1:4 (the molar ratio of LiCl to YCl3 is 2:1), add 20g of isopropanol and a certain amount of zirconium oxide grinding balls (ball-to-material ratio 5:1) into a ball mill. Under the protection of inert gas, rotate forward at a speed of 500rpm / min for 30min and then stop for 10min, then reverse for 30min and then stop for 10min, repeat 30 times in total, and after mixing, vacuum dry into powder, then put it into a tube furnace and sinter it at 200℃ for 5h in an Ar atmosphere. After sintering, the inorganic solid electrolyte solid solution material LLZTYOCl can be obtained.

[0126] Example 5

[0127] LLZTInOCl(aLi 6.5 Ln3Z 1.5 Ta 0.5 O 12 ·bLi2InCl6=

[0128] Li 6.5a+2b La 3a Zr 1.5a Ta 0.5a In b O 12a Cl 6b , a: b = 1: 4) preparation method:

[0129] Weigh a total of 10g of nano-oxide electrolyte materials LLZTO, LiCl and InCl3, where the molar ratio of LLZTO to Li2InCl6 is 1:4 (the molar ratio of LiCl to InCl3 is 2:1), add 20g of isopropanol into a ball mill, and a certain amount of zirconium oxide grinding balls (ball-to-material ratio 5:1). Under the protection of inert gas, rotate forward at a speed of 500rpm / min for 30min and then stop for 10min, then reverse for 30min and then stop for 10min, repeat 30 times in total, and after mixing, vacuum dry into powder, then put it into a tube furnace and sinter it at 200℃ for 5h in an Ar atmosphere. After sintering, the inorganic solid electrolyte solid solution material LLZTInOCl can be obtained.

[0130] Example 6

[0131] LLTZrOCl(aLi 0.33 La 0.56 TiO3·bLi2ZrCl6=Li 0.33a+2b La 0.56a Zr b Ti a O 3a Cl 6b ,

[0132] a:b=1:4) preparation method:

[0133] Weigh a total of 10g of nano-oxide electrolyte materials LLTO, LiCl and ZrCl4, where the molar ratio of LLTO to Li2ZrCl6 is 1:4 (the molar ratio of LiCl to ZrCl4 is 2:1), add 20g of isopropanol into a ball mill, and a certain amount of zirconium oxide grinding balls (ball-to-material ratio 10:1). Under the protection of inert gas, rotate forward at a speed of 500rpm / min for 30min and then stop for 10min, then reverse for 30min and then stop for 10min, repeat 30 times in total, after mixing, vacuum dry into powder, then put it into a tube furnace, sinter at 200℃ for 5h in Ar atmosphere, and after sintering, the inorganic solid electrolyte solid solution material LLTZrOCl can be obtained.

[0134] Comparative Example 1

[0135] Weigh 10g of raw materials LiCl and ZrCl4 (LiCl to ZrCl4 molar ratio 2:1) and add them to a ball mill together with 20g of isopropanol and a certain amount of zirconium oxide grinding balls (ball to material ratio 5:1). Under the protection of inert gas, rotate forward at a speed of 500rpm / min for 30min and then stop for 10min, then reverse for 30min and then stop for 10min, repeat 30 times in total, after mixing, vacuum dry into powder, then put it into a tube furnace, sinter at 200℃ for 5h in Ar atmosphere, and obtain the halide solid electrolyte material LiZrCl after sintering.

[0136] Comparative Example 2

[0137] Weigh 10g of raw materials Al2O3, LiCl and ZrCl4, where the molar ratio of Al2O3 to Li2ZrCl6 is 1:4 (the molar ratio of LiCl to ZrCl4 is 2:1), add 20g of isopropanol and a certain amount of zirconium oxide grinding balls (ball-to-material ratio 10:1) into a ball mill. Under the protection of inert gas, rotate forward at a speed of 500rpm / min for 30min and then stop for 10min, then reverse for 30min and then stop for 10min, repeat 30 times in total, after mixing, vacuum dry into powder, then put it into a tube furnace, sinter at 200℃ for 5h in Ar atmosphere, and after sintering, the inorganic solid electrolyte solid solution material LiZrAlOCl can be obtained.

[0138] Comparative Example 3

[0139] Weigh 10g of raw materials LiCl and ZrCl4 (LiCl to ZrCl4 molar ratio 2:1) and 20g of isopropanol and add them to a ball mill, and a certain amount of zirconium oxide grinding balls (ball to material ratio 10:1). Under the protection of inert gas, rotate forward at a speed of 500rpm / min for 30min and then stop for 10min, then reverse for 30min and stop for 10min, repeat 30 times in total, vacuum dry into powder after mixing, and then put it into a tube furnace, sinter at 200℃ for 5h in Ar atmosphere, and obtain inorganic solid electrolyte solid solution material LiZrCl after sintering. Then a certain amount of LiZrCl is mixed with nanopowder LLZTO, where the molar ratio of LiZrCl to LLZTO is 8:2, and the LLZTO-coated LiZrCl electrolyte material is obtained after mixing.

[0140] Performance Testing

[0141] 1. Ionic conductivity: The inorganic solid electrolytes prepared in the examples and comparative examples were pressed (300 MPa, 10 min) into ceramic sheets with a diameter of 16 mm. After surface polishing, the initial ionic conductivity and the ionic conductivity after being placed in air for 24 h were tested. The test results are shown in Table 1.

[0142] 2. Electrochemical properties: The inorganic solid electrolyte powders prepared in the examples and comparative examples were pressed (300 MPa, 10 min) into ceramic sheets with a diameter of 16 mm. After surface polishing, positive electrode slurry (NCM622: conductive agent: binder = 90:5:5) was coated on one side and molten metal lithium was coated on the other side to prepare button batteries. The electrochemical properties at 25°C, 2.8V-4.3V, discharge gram capacity at 0.1C and 1C were tested. The test results are shown in Table 2.

[0143] Table 1 Ionic conductivity test results of the embodiments and comparative examples

[0144]

[0145] Table 2 Electrochemical performance test results of the embodiments and comparative examples

[0146] Example Gram capacity (0.1C, mAh / g) Gram capacity (1.0C, mAh / g) Example 1 176 160 Example 2 172 158 Example 3 170 157 Example 4 178 165 Example 5 179 167 Example 6 173 162 Comparative Example 1 169 155 Comparative Example 2 136 113 Comparative Example 3 142 118

[0147] From the data in Table 1, it can be seen that the initial ionic conductivity of Li2ZrCl6 in Comparative Example 1 is relatively high, but it is very sensitive in the air, and the ionic conductivity drops significantly after being placed for 24 hours, while the initial ionic conductivity of Examples 1 to 6 is relatively high, and the stability is significantly improved after being placed in the air. This is because the nano-oxide solid-dissolved on the surface of the halide can improve the densification of the ceramic sheet on the one hand, and can also effectively prevent its reaction with the air on the other hand. Although the stability in the air is better by coating LLZTO, it cannot form a highly dense structure, so its initial ionic conductivity is low.

[0148] By comparing Comparative Example 3 with Example 1, it can be seen that Example 1 realizes a coating structure by forming a solid solution between the oxide solid electrolyte and the halide solid electrolyte, which can improve the air stability of the halide solid electrolyte without affecting the conductivity of the halide solid electrolyte itself, while coating the oxide solid electrolyte on the surface of the halide solid electrolyte by the traditional coating method (Comparative Example 3) will affect the conductivity of the halide solid electrolyte, resulting in a significant decrease in the initial conductivity.

[0149] From the data in Table 2, it can be seen that the button cells prepared by the solid electrolytes of Examples 1 to 6 have higher discharge gram capacities at 0.1C and 1C, while Comparative Examples 1 to 3 have lower discharge gram capacities at 0.1C and 1C. This is because, on the one hand, the density and ion conductivity of the solid electrolyte ceramic sheets of Examples 1 to 6 and Comparative Examples 1 to 3 are different, and on the other hand, the stability of the solid electrolyte ceramic sheets of Examples 1 to 6 and Comparative Examples 1 to 3 at high current rates is also different. The oxygen-halogen composite inorganic solid electrolyte prepared by Examples 1 to 6 has better ion conductivity and stability than the halide electrolyte (Comparative Example 1) and the composite inorganic solid electrolyte prepared by the traditional coating method (Comparative Example 3).

[0150] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.

[0151] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. An inorganic solid electrolyte, characterized in that: The inorganic solid electrolyte includes an oxide solid electrolyte and a halide solid electrolyte, and both the oxide solid electrolyte and the halide solid electrolyte are lithium-containing solid electrolytes; Wherein, the oxide solid electrolyte at least partially covers the surface of the halide solid electrolyte; The oxide solid electrolyte and the halide solid electrolyte at least partially form a solid solution state to achieve the coating; The particle size of the oxide solid electrolyte is 100-1000 nm; The molar ratio of the oxide solid electrolyte to the halide solid electrolyte is 1:99 to 90:

10.

2. The inorganic solid electrolyte according to claim 1, characterized in that The halide solid electrolyte has a composition formula of Li x MX y express, Wherein, M represents one or more metal elements, and M includes at least one metal element M1 selected from Zr, In, Y, and Sc; X represents a halogen element; The total number of positive valences of the metal element M is z, y=x+z.

3. The inorganic solid electrolyte according to claim 2, characterized in that The M also includes a doping element M2, and the doping element M2 includes a combination of one or more of Mg, Fe, Mn, Al, Cr, and Ti.

4. The inorganic solid electrolyte according to claim 2 or 3, characterized in that: The X is selected from Br, Cl or I.

5. The inorganic solid electrolyte according to any one of claims 1 to 4, characterized in that: The oxide solid electrolyte is in a crystalline state or an amorphous state.

6. The inorganic solid electrolyte according to any one of claims 1 to 5, characterized in that: The oxide solid electrolyte is selected from at least one of NASICON type, perovskite type, garnet type and LISICON type.

7. A method for preparing an inorganic solid electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mixing the synthetic raw material of the halide solid electrolyte and the oxide solid electrolyte with a solvent to obtain a mixture; High-energy ball milling the mixture to form a precursor; The precursor is sintered to obtain an inorganic solid electrolyte.

8. The preparation method according to claim 7, characterized in that: During the high-energy ball milling process, the rotation speed is 300 to 800 rpm / min, and the ball milling time is 10 to 45 hours.

9. A lithium secondary battery, characterized in that: The lithium secondary battery comprises a positive electrode, a negative electrode and the inorganic solid electrolyte according to any one of claims 1 to 6.

10. The lithium secondary battery according to claim 9, characterized in that: The negative electrode is a lithium negative electrode.

Citation Information

Patent Citations

  • Method for reducing grain boundary impedance and interface impedance of oxide electrolyte

    CN111509293A

  • Solid electrolyte material, preparation method thereof and solid-state lithium battery

    CN112838264A

  • Composite solid electrolyte, preparation method thereof and lithium ion battery

    CN117613368A